A pilot study of bullying and harassment among medical professionals in Pakistan, focussing on psychiatry: need for a medical ombudsman - Gadit, A. A. M. (Journal of medical ethics, 2008)
Background: The magnitude of bullying and harassment among psychiatrists is reportedly high, yet no peer-review published studies addressing this issue could be found. Therefore, it was decided to conduct a pilot study to assess the degree of the problem, the types of bullying/harassment and to provide some insights into the situation.Methods and Principal Findings: Following multiple focus group meetings, a yes/no response type questionnaire was developed to assess the degree and type of bullying and harassment experienced by psychiatrists. Over a 3-month period the questionnaire was administered to a random sample of 60 psychiatrists. 57 out of the 60 psychiatrists reported harassment and bullying. Frequencies of the following response variables are presented in descending order: rumours 40% (n = 24); defamation 20% (n = 12); passing remarks 20% (n = 12); false accusations 15% (n = 9); threats 13.3% (n = 8); verbal abuse 13.3% (n = 8); unjustified complaints 13.3% (n = 8); promotion blocked 13.3% (n = 8); humiliation 13% (n = 8); bad reference given 10% (n = 6); credentials questioned 8.3% (n = 5); physical attacks 5% (n = 3); termination 5% (n = 3); derogatory remarks 1.7% (n = 1) and 1.7% (n = 1) were subjected to personal work. As a result of being subjected to harassment, 66.7% of the psychiatrists did not take any action, whereas 33.3% confronted the person(s) they believed responsible. Asked whether the bullying and harassment caused distress, 18.3% of the psychiatrists did not report any effect, 30% reported mild distress, 40% moderate distress and severe distress was reported by 11.7%.Conclusions: It was concluded that the magnitude of bullying and harassment among psychiatrists may be quite high, as evidenced by this pilot study. There is a need for extensive systematic studies on this subject and to establish strategies to prevent and address this issue at a national and regulatory level.